Exploring the contribution of maternal antibiotics and breastfeeding to development of the infant microbiome and pediatric obesity. Issue 6 (December 2016) - Lemas, Dominick J.; Yee, Shanique; Cacho, Nicole; Miller, Darci; Cardel, Michelle; Gurka, Matthew; Janicke, David; Shenkman, Elizabeth
Summary: Pediatric obesity, a significant public health concern, has been associated with adult premature mortality and the development of type 2 diabetes and cardiovascular disease. Evidence has suggested that the gut microbiota is associated with pediatric obesity. Establishment of the infant gut microbiome is dependent on a dynamic maternal–infant microbiota exchange during early life. The objective of this review is to describe maternal factors such as feeding practices and antibiotic use that may influence the infant gut microbiome and risk for obesity. The complex components in human milk have many nutritional benefits to the infant; however, the microbiome in human milk may be an important factor to help regulate the infant's weight. We discuss maternal antibiotics and the effects on breast milk as critical exposures that alter the infant's gut microbiome and influence the risk of pediatric obesity.